Determining the strategies of teaching Arabic language courses in the Kingdom of Saudi Arabia - Al-Harbi, Amal Bint Nasser; Al-Aridi, Wafa bint Hafez (Journal of Educational and Psychological Sciences, 2021)
The study aimed in addition to the teaching strategies, the study body, and the teaching staff in the management program of a training program, where the result was an intentional sample sample sample consisting of (75) teachers of the Arabic language, and the researcher recommended the formation of Arabic language teachers, and the researcher recommended in The first page for Arabic language teachers, and recommended the modern researcher in listening skills in the Arabic language, and its adoption of an effective method of teaching.
Keywords: Teaching strategy; skill; listening skill; teaching; Arabic language courses